A new species of the subterranean genus Zhijinaphaenops Uéno, 2002, from a Karst Cave in Guizhou, China (Coleoptera: Carabidae: Trechini) - Feng, Xueli; Zhao, Zhengxue; Song, Xiaohui; Xiao, Jie (Zootaxa, 2026)
A new eyeless species, Zhijinaphaenops lianhuaensis sp. nov., has been discovered within Lianhua Cave, Puding County, Anshun City, Guizhou Province. This new species was discovered in the same cave where the paratype specimens of Z. pubescens Uéno & Ran, 2002 were collected earlier. However, comparative examination reveals distinct differences between the two species with respect to pronotum morphology, male genitalia, and elytral size.